Private education and taxes: Is the tax regime for private schools just? - Juan Espindola (Arizona State University, 2016)
This paper describes and evaluates the tax regime that benefits private schools in Mexico, particularly in Mexico City. Its central claim is that this regime is incompatible with educational equality and justice. The main contribution of the paper is to examine primary and secondary empirical sources in light of the normative argument guiding this work. The first section of this work clarifies the central issues that will be addressed in the paper. The second section briefly describes the key features of the Mexican private educational sector and its tax regime. Finally, section three argues that this regime is regressive, and that the moral justifications usually invoked in its defense are untenable.